2022
DOI: 10.1093/cid/ciab1064
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Letermovir Primary Cytomegalovirus Prophylaxis on 1-Year Mortality After Allogeneic Hematopoietic Cell Transplantation: A Retrospective Cohort Study

Abstract: Background CMV seropositive (R+) hematopoietic cell transplant (HCT) recipients have a survival disparity compared with CMV seronegative recipient/donor (R-D-) pairs. We hypothesized that primary letermovir prophylaxis (LET) may abrogate this disparity. We investigated the relationship between LET and mortality at 1year post-HCT. Methods In this retrospective cohort study, we included adult R-D- or R+ patients who received HC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 23 publications
0
16
0
Order By: Relevance
“…In this regard, our interpretation of existing data support that a broader use of letermovir primary prophylaxis in the next future may result into an improvement of the overall transplant outcomes, as suggested by a post-hoc analysis on overall mortality conducted on the patients recruited in the phase III trial of letermovir versus placebo [24]. Moreover, a retrospective single-centre study comparing the outcome of two adult cohorts of patients, transplanted before and after the introduction of letermovir prophylaxis, respectively, showed that the 1-year mortality of letermovir-treated cohort was significantly reduced compared with that of no-letermovir-treated cohort and superimposable to that of CMV negative recipient/donor pairs [25].…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, our interpretation of existing data support that a broader use of letermovir primary prophylaxis in the next future may result into an improvement of the overall transplant outcomes, as suggested by a post-hoc analysis on overall mortality conducted on the patients recruited in the phase III trial of letermovir versus placebo [24]. Moreover, a retrospective single-centre study comparing the outcome of two adult cohorts of patients, transplanted before and after the introduction of letermovir prophylaxis, respectively, showed that the 1-year mortality of letermovir-treated cohort was significantly reduced compared with that of no-letermovir-treated cohort and superimposable to that of CMV negative recipient/donor pairs [25].…”
Section: Discussionmentioning
confidence: 99%
“…The efficacy of letermovir prophylaxis in reducing the risk of csCMVi after HSCT is well established. 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 27 However, high rates of late csCMVi have been observed when letermovir prophylaxis is limited to the first 100 days’ posttransplant, especially in high-risk patient groups such as HLA-disparate donor recipients. 11 , 22 A single-center analysis has shown that extending prophylaxis duration beyond 100 days is highly effective in preventing csCMVi in patients with GVHD, another high-risk patient group.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, our interpretation of existing data support that a broader use of letermovir primary prophylaxis in the next future may result into an improvement of the overall transplant outcomes, as suggested by a post-hoc analysis on overall mortality conducted on the patient recruited in the phase III trial of letermovir versus placebo 24 . Moreover, a retrospective single-centre study comparing the outcome of two adult cohorts of patients, transplanted before and after the introduction of letermovir prophylaxis, respectively, showed that the 1-year mortality of letermovir-treated cohort was signi cantly reduced compared with that of noletermovir-treated cohort and superimposable to that of CMV negative recipient/donor pairs 25 .…”
Section: Discussionmentioning
confidence: 99%